Proposta de implantação da manutenção preventiva em um supermercado do oeste do Paraná - Silva, Diogo Anselmini da (2012)
This project aims to propose a preventive maintenance plan for a supermarket of Paraná. In order to facilitate the control of maintenance services, standardization of procedures, coding and implementation of equipment preventive maintenance, facilitating the management of a maintenance sector. Based on bibliographies and reports of personnel directly involved in maintaining a schedule was created with examples of order service, layout, records and historical records of equipment, operational procedures, lists of parts, control methods, recruitment and division of hand standardization work and maintenance. The same explains the main types of maintenance (planned and unplanned Corrective and Preventive) with emphasis on preventive, demonstrating their importance in a company.